The answer would be:
[tex]43\frac{m}{s}[/tex]
Here is why:
To determine what the final velocity is, we can do this by using the kinematics formula:
[tex]V_{f}=V_{i} +at[/tex]
Where:
Vf = final velocity
Vi = initial velocity
a = acceleration
t = time
In this case, the following are your given:
Vf = unknown
Vi = 25 m/s
a = 6 m/s²
t = 3 s
So just plug that in the equation and solve:
[tex]V_{f}=V_{i} +at[/tex]
[tex]V_{f}=25\frac{m}{s} +(6 \frac{m}{s^{2}})(3s)[/tex]
[tex]V_{f}=25\frac{m}{s} +18 \frac{m}{s}[/tex]
[tex]V_{f}=43\frac{m}{s}[/tex]
So the answer is 43m/s